Chub movement is attracted by the collision sounds associated with spawning activities - Wang, Ya-Lun; Lin, Chia-Yu; Huang, Shih-Pin; Lee, Chia-Yun; Tuanmu, Mao-Ning; Wang, Tzi-Yuan (Zootaxa, 2022)
Cyprinids (carps, chubs and minnows) possess well-developed hearing and high sensitivity to sound pressure. The sensitive hearing may assist cyprinids with searching for food, territory defense, and mating behavior. Many paired fishes violently shake in sand and gravel while spawning in rivers. However, no study has examined the ecological importance of the collision sound made by the behavior. This study examined whether cohabitated chubs (Opsariichthys evolans and Zacco platypus) use the collision sound as a signal to locate spawning events so they can be a male satellite or egg eater. Three types of sounds (i.e., collision sound, music noise and ambient noise) were played with or without jerkbaits at the midstream of the Keelung River, Taiwan during the spawning season in 2018 and 2019. Generalized linear mixed models were then built to examine the effects of the sound types and the presence of jerkbaits on the number of individuals that the two chubs attracted. Results showed significantly different levels of attractiveness among the three sound types, with the collision sound attracting most fishes, including both females and males, followed by music noise and ambient noise. The presence of jerkbaits increased the number of fishes attracted, but the effect was only statistically marginally significant. These results suggest that the collision sound as an acoustic signal may be more important than a visual signal for the chubs to locate spawning events of other mating pairs, probably because of the longer transmission distance of the former. The present study demonstrates the ecological meanings of the collision sounds made in association with spawning activities of the chubs and implies that the native chub's spawning activities may be affected by the introduced Z. platypus. More studies on the interactions between these cohabitated chubs will benefit the conservation of native chubs.